Three decades of declines restructure butterfly communities in the Midwestern United States - Wendy Leuenberger; Jeffrey W. Doser; Michael W. Belitz; Leslie Ries; Nick M. Haddad; Wayne E. Thogmartin; Elise F. Zipkin (Proceedings of the National Academy of Sciences, 2025)
Insects are declining worldwide. These declines have been documented across taxonomic groups and are worrisome given ecosystem services provided by insects. Long-term data have illuminated butterfly declines across geographic regions. However, critical questions remain on how butterfly declines are distributed across species and functional groups, limiting effective conservation. Here, we show unprecedented changes in butterfly biodiversity resulting from 32 y of species levels declines throughout the Midwestern United States. No species increased over the three-decade study period and abundance declined across every functional group (e.g., rare, common, migratory, resident; annual mean trend: −0.9 to −2.3% per year). Species richness declined across all but one functional group, with concomitant increases in evenness (e.g., abundance among species) in several groups resulting from steeper losses in abundance for common species (abundance: −1.9% per year; richness: −0.04% per year) as compared to rare species (abundance: −0.9% per year; richness: −1.33% per year). Our results paint a bleaker picture than other butterfly studies likely due to our long time series of data and ability to include rare species. Such widespread declines undoubtedly affect other trophic levels and ecosystem services. Focusing risk assessments and management interventions only on rare species is likely to be insufficient given broad declines across species, which have fundamentally restructured butterfly communities in the region. As such, conservation efforts should shift focus to species assemblages and entire communities when possible.